FPGA Implementation and Design of a Hybrid Chaos-AES Color Image Encryption Algorithm - Yang, Cheng-Hsiung; Chien, Yu-Sheng (Symmetry (Basel), 2020)
In this paper, we propose an image encryption algorithm based on four-dimensional chaotic system to generate key and improve advanced encryption standard. The encryption algorithm is optimized by using the pipeline and parallel computing features of Field Programmable Gate Array (FPGA). First, the chaotic system is used as a key generator for the encryption algorithm. Next, in the improved advanced encryption standard, ShiftRows and SubByres are modified with Spin-Sort and Cubic S-Box, and the round of encryption is reduced. We implement the encryption algorithm and the wired image transmission system to the ARM-based SoC-FPGA. The HPS software runs on Linux and is used to control the FPGA encryption algorithm and image transmission. Finally, the results from the encryption security analysis show that the proposed image encryption algorithm is safe and effective.